1997
DOI: 10.1016/s0039-6028(96)01099-0
|View full text |Cite
|
Sign up to set email alerts
|

The adsorption site and orientation of CH3S and sulfur on Ni(001) using angle-resolved X-ray photoelectron spectroscopy

Abstract: Photoelectron diffraction from the S 2p core level has been used to determine the adsorption site and orientation of sulfur and methyl thiolate (CH3S) on Ni(001) by comparing the experimental data with the results of multiple scattering calculations. The theory was initially checked for atomic S, which is known to adsorb in the four-fold hollow site on Ni(001), and the results corresponded to the correct geometry. Comparison of calculated spectra with the experimental data indicates that chemisorbed atomic sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…Also significantly different binding energies (BE) for the S 2p3/2 component have been reported for thiols chemisorbed on Ni ranging from 161.8 to 163.3 eV. 21,26,27 Another point to consider is that atomic S in the form of NiS exhibits a BE range from 161.0 to 162.2 eV overlapping in some extent the BE range expected for thiolates. 26,28 On the basis of our data we can not therefore discard the presence of some amount of S in a mixed S/octanethiol monolayer which could explain the enhanced HER reaction observed in our samples.…”
Section: Results and Analysismentioning
confidence: 99%
“…Also significantly different binding energies (BE) for the S 2p3/2 component have been reported for thiols chemisorbed on Ni ranging from 161.8 to 163.3 eV. 21,26,27 Another point to consider is that atomic S in the form of NiS exhibits a BE range from 161.0 to 162.2 eV overlapping in some extent the BE range expected for thiolates. 26,28 On the basis of our data we can not therefore discard the presence of some amount of S in a mixed S/octanethiol monolayer which could explain the enhanced HER reaction observed in our samples.…”
Section: Results and Analysismentioning
confidence: 99%
“…It has also been reported that organic thiocyanates yield thiol SAMs on some metals. 77 All these molecules can be self-assembled on different metallic surfaces, like Au (the most important one and the aim of this review), but also Ag, 10,[78][79][80][81][82][83][84][85][86][87] Cu, 70,[88][89][90] Pd, [91][92][93][94][95][96] Pt, 95 Ni [97][98][99][100][101][102][103] and Fe. 104,105 In all cases oxide-free surfaces are needed to selfassemble the thiol monolayer.…”
Section: General Aspects Of Thiol and Dithiol Sams On Goldmentioning
confidence: 99%
“…C-S bond scission has already been reported for adsorbed thiolates and determined that the extent of scission depends on the initial substrate condition and alkanethiol coverage. 195,[197][198][199] The onset of S-C bond scission for low MT exposures was reported to occur well below room temperature; [197][198][199] however, in the presence of pre-adsorbed S the reaction takes place above room temperature. 197,198,200 Also, benzenethiolate adsorbed on Ni (111) starts to form benzene at 290 K 200 a reaction where the adsorbed H from the S-H bond scission plays a key role.…”
Section: Nickelmentioning
confidence: 99%
“…The adsorption of MT on the (100) plane of Ni was also investigated at 100 K. 199 Results are qualitatively similar to those obtained for atomic S on this surface, which is known to adsorb in the fourfold hollow site on Ni (100). Attempts to optimize BT on the (100) surface in c(2 Â 2) with q ¼ 0.50 failed, likely due to the small RSc interdistance (less than 0.35 nm) leading to repulsion between hydrocarbon chains.…”
Section: Nickelmentioning
confidence: 99%